2010
DOI: 10.1183/09031936.00039510
|View full text |Cite
|
Sign up to set email alerts
|

Trimodality therapy for malignant pleural mesothelioma: results from an EORTC phase II multicentre trial

Abstract: The European Organisation for Research and Treatment of Cancer (EORTC; protocol 08031) phase II trial investigated the feasibility of trimodality therapy consisting of induction chemotherapy followed by extrapleural pneumonectomy and post-operative radiotherapy in patients with malignant pleural mesothelioma (with a severity of cT3N1M0 or less).Induction chemotherapy consisted of three courses of cisplatin 75 mg?m -2 and pemetrexed 500 mg?m -2 . Nonprogressing patients underwent extrapleural pneumonectomy foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(140 citation statements)
references
References 29 publications
8
127
3
2
Order By: Relevance
“…The EORTC initiated a phase II trial to evaluate the feasibility of trimodal therapy in a multicentre international setting (EORTC 08031) with clearly defined timelines [43]. Patients with pathologically proven mesothelioma of stage cT3N1M0 or less underwent induction chemotherapy consisting of three cycles of cisplatin and pemetrexed followed by EPP within 21-56 days after the last dose of chemotherapy if there was no progressive disease and no unacceptable toxicity.…”
Section: Combined-modality Therapymentioning
confidence: 99%
“…The EORTC initiated a phase II trial to evaluate the feasibility of trimodal therapy in a multicentre international setting (EORTC 08031) with clearly defined timelines [43]. Patients with pathologically proven mesothelioma of stage cT3N1M0 or less underwent induction chemotherapy consisting of three cycles of cisplatin and pemetrexed followed by EPP within 21-56 days after the last dose of chemotherapy if there was no progressive disease and no unacceptable toxicity.…”
Section: Combined-modality Therapymentioning
confidence: 99%
“…Their apparent benefit is based on completed treatments rather than on intention to treat; patients who do poorly do not complete the protocol and are thus not included in the final analysis (2). Nevertheless, their results can be used to shape future surgical trial protocols by excluding poorly tolerated regimes i.e., European Organisation for Research and Treatment of Cancer (EORTC) trial 08031 which showed the difficulty in tri-modality therapy including extrapleural pneumonectomy (EPP) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Younger patients with good performance status, epithelioid histology, and localized resectable disease can generally be offered multimodality therapy with systemic chemotherapy, surgical resection, and sometimes radiation therapy (28,29). Another article in this issue of Translational Lung Cancer Research discusses surgical options for MPM; however, we will briefly mention here that surgical options are generally limited to patients with the epithelioid subtype of MPM and consist of pleurectomy/decortication (P/D) with mediastinal lymph node sampling or extrapleural pneumonectomy (EPP).…”
Section: Introductionmentioning
confidence: 99%